Selective aqueous ammonia sensors using electrochemical stripping and capacitive detection. Issue 12 (7th October 2021) - Lalwani, Anand V.; Dong, Hang; Mu, Linchao; Woo, Kelly; Johnson, Hunter A.; Holliday, Max A.; Guo, Jinyu; Senesky, Debbie G.; Tarpeh, William A.
Abstract: Managing waterborne ammonia–nitrogen pollution requires monitoring distributed wastewater nitrogen discharges. In this study, we demonstrated and investigated a proof‐of‐concept sensor that combines selective electrochemical separation and sensitive capacitive detection for sensing total ammonia nitrogen (TAN). By varying TAN concentration in synthetic ammonia‐polluted water (up to 50 mg/L), we selectively separated ammonia nitrogen from feedwater into a sulfuric acid solution, in which capacitance decreased linearly with increasing TAN ( R 2  > 0.99). Experimental observations were supported by theoretical explanations for the decrease in capacitance as ammonia absorbs into the sulfuric acid solution and abstracts protons. Capacitive detection facilitated TAN sensing at higher acid concentrations (up to 0.5 M H2 SO4 ) than conductivity detection (up to 0.01 M H2 SO4 ), which enables sensitive sensors with larger TAN detection ranges, longer deployment, and less complexity. Results from this study provide evidence of the use of selective separations and their transport mechanisms for environmental sensing applications.